2019
DOI: 10.1002/ijgo.12812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of length of hospital stay on infection and readmission after minimally invasive hysterectomy

Abstract: Objective To assess the effect of length of hospital stay on postoperative outcomes after minimally invasive hysterectomy. Methods A retrospective cohort analysis was conducted of women who underwent minimally invasive hysterectomy (vaginal or laparoscopic) for benign conditions between January 1, 2014 and December 31, 2016, using the American College of Surgeons National Surgical Quality Improvement Program database. Patient information and 30‐day outcomes were compared using multivariable logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
(30 reference statements)
0
7
0
3
Order By: Relevance
“…program and lower narcotic use are associated with an increased SDD, although more studies are needed to elucidate such findings. Previous studies have demonstrated that SDD is associated with similar rates of patient satisfaction, without increased infection or readmission rates, and significant savings in healthcare costs [5,12,13]. Thus, identification of factors affecting SDD allows a rational approach to increasing the number of patients discharged the day of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…program and lower narcotic use are associated with an increased SDD, although more studies are needed to elucidate such findings. Previous studies have demonstrated that SDD is associated with similar rates of patient satisfaction, without increased infection or readmission rates, and significant savings in healthcare costs [5,12,13]. Thus, identification of factors affecting SDD allows a rational approach to increasing the number of patients discharged the day of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…SDD after laparoscopy is a safe alternative to admitting patients overnight for postoperative observation [10,11]. It has been demonstrated that SDD after surgery is neither associated with an increased risk of infection nor an increased chance of readmission [12,13]. Moreover, SDD provides substantial healthcare cost savings and results in similar rates of patient satisfaction [5].…”
mentioning
confidence: 99%
“…Strengths of this study included the use of the American College of Surgeons−NSQIP national database with its standardized collection of comprehensive patient data from a variety of hospitals. The database has been widely used to assess postsurgical outcomes for hysterectomy and other surgical procedures [4,22,23]. Furthermore, the database's targeted hysterectomy data file allowed us to account for important factors such as uterine weight that might have affected the hysterectomy route and postsurgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Respecto a la frecuencia de rehospitalización nuestros resultados son similares a los informados por Lassen et al 13 , quienes documentaron un 12% de reingresos por urgencias, y Maheux et al 14 que informan un 17% de consultas no planeadas en pacientes que egresaron el día de la cirugía. Por otra parte, es mayor que la informada por Korsholm y Col, quienes informan en la RS de 15 estudios observacionales un rango de rehospitalización del 3,3% en pacientes en los que no es claro el tiempo de corte de la salida, y 5,5% de readmisiones en aquellos en que es claro el límite para definición de salida temprana 11 , y a la informada por Sheyn y et al en un estudio de corte retrospectivo realizado con la base de datos del Colegio Americano de Cirujanos (CAC), quienes informan una frecuencia de readmisión en las mujeres con salida temprana del 2,2% para el periodo comprendido entre el 2010 y 2014 15 , y también superior al informado por Schiff et al, quienes informan una frecuencia de complicaciones del 1,7% en la misma base de datos con pacientes operados entre el 2014 y 2016 16 .…”
Section: Discussionunclassified
“…Respecto a la frecuencia de complicaciones mayores, nuestros resultados son mayores a lo reportado por Maheux y et al 14 ), con una frecuencia del 10%, todas menores, y a las de Lassen, quien informa una frecuencia de complicaciones menores del 15% 13 . Schiff, en la base de datos del CAC, informa una frecuencia del 3,6%, de estas, el 2% corresponden a infección urinaria, el 1,6 % a infección del sitio quirúrgico, principalmente infección superficial 16 . Nuestra frecuencia de complicaciones es inferior a lo presentado por Calle et al en Colombia, quienes informaron una tasa de complicaciones del 11,8%, de las cuales el 15% presentó infección de cúpula vaginal, 3,3% hematoma de cúpula, 1,6% sangrado tardío de cúpula, 1,6% de infección urinaria y 0,3% de dehiscencia de cúpula, con un reingreso del 3,3% similar a lo reportado en el presente estudio 17 .…”
Section: Discussionunclassified